Menembus Dominasi: Menelaah Pemahaman Jemaat dan Upaya Dekonstruksi terhadap Teks-Teks Kekerasan dalam Alkitab serta Implikasinya dalam Pendidikan Anak di Jemaat Germita Bukit Sinai Melonguane Barat - Anita Inggrith Tuela; Frety Cassia Udang; Yolanda Nany Palar (Peneliti.net, 2022)
This study aims to describe the violence in the Bible that frames the portrait of people's journey, encounter and association with God. Traces of blood, traces of domination, and traces of discrimination are the things that characterize the biblical narrative. Its presence in the Bible often makes it a reference to legitimize violence or also makes the congregation confused in understanding God and his intentions. In addition, this study also seeks to understand God's intention so that readers can eliminate or at least obscure the topic of violence as an effort of theodicy. This study uses a qualitative approach with data collection techniques through unstructured interviews and literature study. Based on the research results obtained from the congregation's answers regarding the understanding of violent texts, it is illustrated that the congregation is still conceptualized on the dominant understanding as the result of standard dogmatic interpretations that have been passed down for so long. It is inherent as a standard paradigm for the congregation. The congregation prefers to see it from a wider angle so that taboos and unusual things that appear in the text can be marginalized. The results of the congregation's reading of violent texts became the entry point for this research effort to deconstruct these texts. This deconstruction effort is a contribution of creative critical thinking to the repertoire of people's understanding of violent texts in the Bible. This research is expected to be able to build awareness that claims of violence in the Bible are one-sided claims that ignore the merits of the biblical text and the laws of the Bible comprehensively. In addition, the results of this study have implications for children's education as an effort to provide an understanding of violence in the Bible, so that they can understand God's intent in texts with nuances of violence in the Bible. In fact, they can understand the negative impact of acts of violence.